PROPAGATION OF AXISYMMETRIC LONGITUDINAL WAVES IN A FINITELY PRESTRAINED CIRCULAR CYLINDER IMBEDDED IN A FINITELY PRESTRAINED INFINITE ELASTIC BODY - Akbarov, S. D.; Guliev, M. S. (SPRINGER, 2008)
Within the framework of a piecewise homogeneous body model and with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies (TLTEWISB), the propagation of axisymmetric longitudinal waves in a finitely prestrained circular cylinder (fiber) imbedded in a finitely prestrained infinite elastic body (matrix) is investigated. It is assumed that the fiber and matrix materials have the same density and are incompressible. The stress-strain relations for them are given through the Treloar potential. Numerical results regarding the influence of initial strains in the fiber and matrix on wave dispersion are presented and discussed. These results are obtained for the following cases: the fiber and matrix are both without initial strains; only the fiber is prestretched; only the matrix is prestretched; the fiber and matrix are both prestretched simultaneously; the fiber and matrix are both precompressed simultaneously.
Keywords: initial strain; incompressible material; unidirectional fibrous composite; wave dispersion; wave propagation; INTERFACE STRESS-FIELD; DEFORMATIONS; CONSTANTS; SLAB; Mechanics; Materials Science; Polymer Science